Physiology : a review with questions and explanations - Benjamin Hsu ... [et al.].; Tadlock, Charles H.; Assef, Saied; Percelay, Jack M. (Boston, Massachusetts : Little, Brown and Company, 1987)
This book was written by medical students from the stanford and university of california, san francisco medical schools. It reviews the essential points covered in a standard medical physiology course and in the physiology section of the National Medical Board Examiantion (Part 1).
1. General physiology -- 2. Endocrine physiology -- 3. Gastrointestinal physiology -- 4. Cardiovascular physiology -- 5. Renal physiology -- 6. Respiratory physiology -- 7. Acid-base physiology -- 8. Neurophysiology.
Includes bibliographical references and index.
Keywords: PHYSIOLOGY